Realistic 3D hydrodynamics simulations find significant turbulent entrainment in massive stars. Issue 3 (23rd July 2022) - Rizzuti, F; Hirschi, R; Georgy, C; Arnett, W D; Meakin, C; Murphy, A StJ
ABSTRACT: Our understanding of stellar structure and evolution coming from one-dimensional (1D) stellar models is limited by uncertainties related to multidimensional processes taking place in stellar interiors. 1D models, however, can now be tested and improved with the help of detailed three-dimensional (3D) hydrodynamics models, which can reproduce complex multidimensional processes over short time-scales, thanks to the recent advances in computing resources. Among these processes, turbulent entrainment leading to mixing across convective boundaries is one of the least understood and most impactful. Here, we present the results from a set of hydrodynamics simulations of the neon-burning shell in a massive star, and interpret them in the framework of the turbulent entrainment law from geophysics. Our simulations differ from previous studies in their unprecedented degree of realism in reproducing the stellar environment. Importantly, the strong entrainment found in the simulations highlights the major flaws of the current implementation of convective boundary mixing in 1D stellar models. This study therefore calls for major revisions of how convective boundaries are modelled in 1D, and in particular the implementation of entrainment in these models. This will have important implications for supernova theory, nucleosynthesis, neutron stars, and black holes physics.